2016
DOI: 10.1038/srep37249
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Cyclacenes from TAO-DFT

Abstract: Owing to the presence of strong static correlation effects, accurate prediction of the electronic properties (e.g., the singlet-triplet energy gaps, vertical ionization potentials, vertical electron affinities, fundamental gaps, symmetrized von Neumann entropy, active orbital occupation numbers, and real-space representation of active orbitals) of cyclacenes with n fused benzene rings (n = 4–100) has posed a great challenge to traditional electronic structure methods. To meet the challenge, we study these prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 60 publications
8
105
2
Order By: Relevance
“…Besides, existing XC density functionals in KS-DFT may also be adopted in TAO-DFT. Due to its computational efficiency and reasonable accuracy for large systems with strong static correlation, TAO-DFT has been successfully applied to the study of several strongly correlated electron systems at the nanoscale [14,[49][50][51], which are typically regarded as "challenging systems" for traditional electronic structure methods (e.g., KS-DFT with conventional XC density functionals and single-reference ab initio methods) [44]. Accordingly, TAO-DFT can be an ideal theoretical method for studying the electronic properties of Li 2 C n .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, existing XC density functionals in KS-DFT may also be adopted in TAO-DFT. Due to its computational efficiency and reasonable accuracy for large systems with strong static correlation, TAO-DFT has been successfully applied to the study of several strongly correlated electron systems at the nanoscale [14,[49][50][51], which are typically regarded as "challenging systems" for traditional electronic structure methods (e.g., KS-DFT with conventional XC density functionals and single-reference ab initio methods) [44]. Accordingly, TAO-DFT can be an ideal theoretical method for studying the electronic properties of Li 2 C n .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, linear n-acenes (C 4n+2 H 2n+4 ), containing n linearly fused benzene rings (see Figure 10), have attracted considerable interest in the research community owing to their promising electronic properties [20,21,[45][46][47][48][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124]. The electronic properties of nacenes have been found to be highly dependent on the chain lengths.…”
Section: Electronic Properties Of Linear Acenesmentioning
confidence: 99%
“…To reduce the SCE problems with low computational complexity, we have recently developed thermally-assisted-occupation density functional theory (TAO-DFT) [20,21], an efficient electronic structure method for studying the ground-state properties of very large systems (e.g., containing up to a few thousand electrons) with strong static correlation effects [45][46][47][48]. Unlike finite-temperature DFT [49], TAO-DFT is developed for ground-state systems at zero temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Besides experimental work on [ n ]cyclacenes, several computational studies using semi‐empirical methods and ab initio methods have been carried out on these systems. The semi‐empirical work was focused both on an analysis of the structural properties of the cyclacenes as well as the behavior of electronic properties such as the HOMO–LUMO gap as a function of the system size parameter n .…”
Section: Introductionmentioning
confidence: 99%
“…First principles ab initio studies mainly concentrated on the ground‐state character of the wave function and the corresponding excitation energy to the first electronically excited state. Recent studies have shown that the ground state is a singlet state of open‐shell character, with an increasing number of unpaired electrons with increasing system size. This fact in particular, is believed as one of the causes of the difficulties in the synthesis of cyclacenes as it was already argued in the reviews aforementioned.…”
Section: Introductionmentioning
confidence: 99%